Peningkatan Kesejahteraan Pendapat Asli Desa (PAD) melalui Pendirian dan Pelatihan Pojok Digital UMKM di Kabupaten Sumedang - Andreas Recki Prasetyo; Camelia Rizki Agrina (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The SMEs Go-Digital Corner is one of the outcomes of collaboration between the Regional Development Planning Agency (BAPPEDA) of Sumedang and Oorange & DIGITS UNPAD - the Business Incubator Center of Universitas Padjadjaran. It represents a Pentahelix program collaboration for the implementation of the SMEs Go Digital program in Sumedang. The overall objective of this program is to provide encouragement and stimulus to UMKM actors in Sumedang, particularly in 22 villages affected by Covid-19. The general goal of this initiative is to help businesses in these 22 villages sustain and grow by utilizing online sales and facilitating logistics delivery. This initiative involves the participation of 11 lecturers from various faculties at Universitas Padjadjaran, 110 integrated Community Service Program (KKN) students, SMEs actors, BUMDes executives, and internet service providers. The digital corner activities took place from September 2021 to February 2022. The outcomes of this initiative include the establishment of 22 internet sources that can be utilized by the community in these 22 villages, comprising 14 Indihome packages and 8 Orbit packages. These 22 points can be maximized to create digital corners through various activities to enhance the Village-Owned Enterprises' revenue through optimal management by BUMDes.